Authentic or not : the Filipino food revolution [videorecording (DVD)] - Soriano, Chris; Torres, Rhandy; Dahilig, Ina; Soriano, Hillary (Gravitas Ventures, 2025)
Explore the clash between traditional Filipino dishes and modern innovations, celebrating how this vibrant cuisine connects people, preserves culture, and evolves bridging the past, present, and future of Filipino food.